The effect of eight weeks of high-intensity interval training on changes in the levels of leptin, adiponectin and insulin levels in male Wistar rats - Hossein Pirani; Omidreza Salehi; Kayvan Khoramipour; Fereshteh Golestaneh (مجله دانشگاه علوم پزشکی بیرجند, 2023)
Background and Aims: Obesity leads to impaired secretion and expression of adipokines in humans and causes the onset of type 2 diabetes. Although the role of regular exercise in the prevention of metabolic diseases has been reported, the mechanism of high-intensity exercise is still not well understood. Therefore, the aim of the present study was to investigate the effects of 8 weeks of high-intensity interval training on the changes in insulin, leptin and adiponectin levels in male Wistar rats with type 2 diabetes. Materials and Methods: In this experimental study 20 male Wistar rats aged 8-10 weeks were randomly divided into four groups: Control, type 2 diabetes, exercise, and diabetes-exercise. Type 2 diabetes was induced by a high-fat diet and a single dose of streptozotocin (STZ). The rats in the exercise and diabetes-exercise groups completed 8 weeks of HIIT training (running at an intensity of 85-95% of maximum speed, intervals of 4-10). Insulin, adiponectin and leptin levels were measured in serum. Homeostasis Model Assessment for Insulin Resistance (HOMA-IR), the Homeostasis Model Assessment for Insulin Resistance-beta (HOMA-β) and the Quantitative Assessment of Insulin Sensitivity Index (QUICKI) were calculated to assess insulin resistance and sensitivity. Results: Diabetes decreased the level of insulin, adiponectin and leptin in serum. HIIT reversed the impairments caused by diabetes. HOMA-IR, HOMA-β and QUICKI also improved in the diabetes-exercise groups. Conclusion: Overall, our results confirmed that diabetes has detrimental effects on serum leptin, adiponectin and insulin indices and that HIIT training can improve these disorders.